PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH BERDASARKAN JUAL BELI DI BAWAH TANGAN (Kajian Terhadap Putusan Nomor: 1860K/Pdt/2005) - Utami, Ketut Dezy Ari (Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract This thesis behind this is the norm of any conflict between the sale and purchase agreement made ââby the Plaintiff husband (deceased Suwadi) with Sri Lestari sealed with receipt in Decision No. 1860 K/Pdt/2005 with the principle of legal certainty. The problem studied in this thesis are: 1) Is the sale of land under the hand without the presence of witnesses can be justified by the law. 2) What are the forms of legal protection of land rights holders in the sale and purchase under the hand without the presence of witnesses. To answer the problem studied, the authors use the method of normative legal approach. Based on the results of the study, the authors obtained answers to existing problems, namely the purchase agreement sealed on top of the basic elements of the agreement have met or commonly referred to the